1972
DOI: 10.1093/genetics/72.4.551
|View full text |Cite
|
Sign up to set email alerts
|

MUTATOR GENE STUDIES IN ESCHERICHIA COLI: THE mutS GENE

Abstract: We report here on a study of a mutator gene (mutS) that causes transition mutations in Escherichia coli. We have used the trpA system to show that A:T→G:C and G:C→A:T transitions occur. Not all A:T pairs are equally susceptible to mutS action however, since the A:T pair at the trpA223 site reverts at a frequency similar to, if not identical with, the frequency in a mut  + background. Presumably this is a consequence of neighboring bases, because other A:T pairs are reverted by mutS in the same gene; and an A:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1973
1973
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Finally, the difference in our estimates from those of Kibota & Lynch (1996) could also be due to the type of mutations that are increased by a deficiency in the mismatch repair genes. It is known that strains without a functional mutS gene have a higher rate of transitions (Cox et al 1972) and these mutations might, on average, have a more deleterious effect than the mutations to which the wild-type strains are exposed. Interestingly, when analysing mutations caused by random transposon insertions (involving the Tn10 element), Elena & Lenski (1997) estimated a mean s d of about 0.03, which is similar to our estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the difference in our estimates from those of Kibota & Lynch (1996) could also be due to the type of mutations that are increased by a deficiency in the mismatch repair genes. It is known that strains without a functional mutS gene have a higher rate of transitions (Cox et al 1972) and these mutations might, on average, have a more deleterious effect than the mutations to which the wild-type strains are exposed. Interestingly, when analysing mutations caused by random transposon insertions (involving the Tn10 element), Elena & Lenski (1997) estimated a mean s d of about 0.03, which is similar to our estimate.…”
Section: Discussionmentioning
confidence: 99%
“…In bacteria, deletion of MMR genes results in a several hundred-fold increase in mutation frequency (Cox et al, 1972). In humans, several primary tumors from cancers including hereditary nonpolyposis colorectal carcinoma (HNPCC) and Turcot syndrome (Fishel et al, 1993;Hamilton et al, 1995) have MMR defects, suggesting that increased mutation frequency could contribute to the development of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Treffers' mutator in E. coli K-12 (TREFFERS, SPINELLI and BELSER 1954) causes a unidirectional change-an AT -) CG transversion (YANOFSKY, Cox and HORN 1966). More recently, Cox, DEGNEN and SCHEPPE (1972) have demonstrated that another E. coli mutator gene, mutS1, yields transitions, confirming the mutagen specificity work of SIEGEL and BRYSON (1 964). However, they showed that not all A: T pairs are equally susceptible; thus, nearest neighbors may influence the mutator action.…”
mentioning
confidence: 76%